(untitled) (Research, Society and Development, 2021)
Introduction: Frontline nurses face an enormous workload, long-term fatigue, threat of infection, and frustration with the death of patients they care for. Objective: To investigate the current evidence on the emergence of psychiatric conditions in nurses working in Intensive Care Units during the Covid-19 pandemic. Methodology: Integrative review study with systematic search, performed in PubMed, Embase, Cochrane Wiley, and Virtual Health Library (VHL) databases. Inclusion criteria were: (1) electronic articles, (2) available in full, (3) in Portuguese, English and/or Spanish. Abstracts, letters to the editor and studies that were not related to the theme were excluded. Results: After applying the eligibility criteria, 21 articles were included in the study. The main risk factors found were: Work in critical care for patients with Covid-19, Use of biosafety equipment, Hospital infrastructure; Inadequate provision of Personal Protective Equipment, Age, gender, marital status, specialty and proximity to Covid-19 patients; Impossibility to meet the psycho-social-emotional needs of patients and families; Difficulty in externalizing your emotions; Lack of professional experience and Fear of contracting the virus and infecting others. The main risk factors for the outcomes mentioned above were: Emotional exhaustion; Psychological stress; anxiety; insomnia; fear; anger and frustration. Conclusions: The nurses working in the ICU during the Covid-19 pandemic presented psychiatric disorders, with emotional stress as the main causal factors, generated by structural and organizational inadequacies in health institutions.